Investigation of microtremor motion variation by Nakamura’S H/V spectral ratio method - Tien, Hung Nguyen -; Nguyen-Hong, Phuong; Nguyen-Le, Minh; Kuo-Liang, Wen; Tran-An, Nguyen (Vietnam Journal of Marine Science and Technology, 2017)
In this study, the variation of microtremor motion is investigated using observation data in Hanoi and Vung Tau cities. The results of observation conducted by times and by seismometers are processed using the Nakamura's H/V spectral ratio method and compared. For investigation, the observations have been conducted with frequency of 27 observations per hour, 22 observations per month, 4 simultaneous observations using both Servo and K2 seismometers, and 12 simultaneous observation using 7 Servo seismometers. The results of data analysis show that the values of dominant frequency and shapes of the H/V spectral ratio obtained are similar in the frequency range from 0.4 Hz to 5 Hz, especially on the dominant frequency domain. The results confirm that the microtremor variation observations can be carried out with one observation time or by multiple seismometers.